Effectiveness of en-masse retraction using midpalatal miniscrews and a modified transpalatal arch: Treatment duration and dentoskeletal changes - Lee, Jungkil (Korean Association of Orthodontists, 2014)
OBJECTIVE: The purpose of this study was to compare the treatment duration and dentoskeletal changes between two different anchorage systems used to treat maxillary dentoalveolar protrusion and to examine the effectiveness of en-masse retraction using two miniscrews placed in the midpalatal suture. METHODS: Fifty-seven patients (9 men, 48 women), who had undergone level anchorage system treatment at Aichi-Gakuin University Dental Hospital (Nagoya, Japan) were divided into two groups according to the method of maxillary posterior anchorage reinforcement: midpalatal miniscrews (25 patients, mean age 22 years) and conventional anchorage (32 patients, mean age 19 years). The en-masse retraction period, overall treatment duration, pre-treatment effective ANB angle, and change in the effective ANB angle were compared with an independent-samples t-test. RESULTS: Compared to the headgear group, the duration of en-masse retraction was longer by approximately 4 months in the miniscrew group (p < 0.001). However, we found no significant difference in the total treatment duration between the groups. Moreover, a greater change in the effective ANB angle was observed in patients treated with miniscrews than in those treated with the conventional method (p < 0.05). CONCLUSIONS: The level anchorage system treatment using miniscrews placed in the midpalatal area will allow orthodontists more time to control the anterior teeth during en-masse retraction, without increasing the total treatment duration. Furthermore, it achieves better dentoskeletal control than does the conventional anchorage method, thereby improving the quality of the treatment results.